STRUT and TIE MODEL SEBAGAI ALTERNATIF PERANCANGAN STRUKTUR BETON BERTULANG - Yuzuar Afrizal (Universitas Bengkulu, 2019)
Design of concrete structures according to the applicable standard is to use the principle of the planning section of the load moment based on the principles of Bernoulli and Navier. Considered linear strain distribution and is considered still valid even though cross-section has been cracked and the planning sectionof the burden of a separate shear forces with the principle of Vc + Vs. The number of cases for the structural elements that have a fairly complicated shape will cause a problem in its design. This happens to the elements - structural elements such as high beam, corbel, beams with fairly abrupt changes in the dimensions, etc. This is evident from the occurrence of non-linear strain distribution so that it can no longer planned in a standard way. Planning is done sometimes only be approach with the regulations - regulations to existing standards, although sometimes there is a significant difference, one alternative approach to deal with is using Strut and Tie Model approach.